Particularities Of Visual Metaphors In Advertising Campaigns About Ecological Problems - Antonova, Olha; Sokolov, Maksym (My University, 2021)
The article is dedicated to the peculiarities of visual metaphors usage in the design of foreign public service announcement campaigns about ecological problems. The specifics of graphic and expressive means of public service announcements against the destruction of forest resources is analysed, typical types of visual metaphors used in public service announcement materials in campaigns of WWF and other world public organizations about this topic are distinguished. It was found that the main implementation element of authors’ communicative strategy in public service announcement materials is the graphic part of advertising, which is based on a metaphorical understanding of reality, and the text serves as an explanatory addition to it. Visual content can be largely outspoken, cruel, and appealing to guilt and fear, which ensures the impact of suggestive influence of public service announcement products and serves as a factor of effectiveness for a public service announcement campaign about this problem.
Keywords: graphic and expressive means of public service announcement; influence of public service announcement; creolized text; design of advertising; visual metaphor; візуальна метафорика; зображально-виражальні засоби реклами; впливогенність реклами; креолізований текст; дизайн реклами; кафедра маркетингу